Speculating on London's housing future: The rise of global corporate landlords in 'post-crisis' urban landscapes. Issue 2 (3rd March 2016) - Beswick, Joe; Alexandri, Georgia; Byrne, Michael; Vives-Miró, Sònia; Fields, Desiree; Hodkinson, Stuart; Janoschka, Michael
Abstract : London's housing crisis is rooted in a neo-liberal urban project to recommodify and financialise housing and land in a global city. But where exactly is the crisis heading? What future is being prepared for London's urban dwellers? How can we learn from other country and city contexts to usefully speculate about London's housing future? In this paper, we bring together recent evidence and insights from the rise of what we call 'global corporate landlords' (GCLs) in 'post-crisis' urban landscapes in North America and Europe to argue that London's housing crisis—and the policies and processes impelling and intervening in it—could represent a key moment in shaping the city's long-term housing future. We trace the variegated ways in which private equity firms and institutional investors have exploited distressed housing markets and the new profitable opportunities created by states and supra-national bodies in coming to the rescue of capitalism in the USA, Spain, Ireland and Greece in response to the global financial crisis of 2007–2008. We then apply that analysis to emerging developments in the political economy of London's housing system, arguing that despite having a very low presence in the London residential property market and facing major entry barriers, GCLs are starting to position themselves in preparation for potential entry points such as the new privatisation threat to public and social rented housing.